Perilaku Kepemimpinan Yang Efektif Model 3 Dimensi: Berorientasi Pada Tugas, Hubungan, Dan Perubahan - Ahmad Saifudin (Prodi Manajemen Pendidikan Islam STAI Darussalam, 2020)
Leadership behavior seems to be the basic thing that must be learned, especially for those who hold leadership and or manager roles. Although not dismissing anyone to explore it. Most of us agree that a good organization will not exist without good people. And the central role of